Study of serum carbonic anhydrase activity, uric acid, C-reactive protein levels and lipid parameters in patients with Psoriasis - Das, S; Biswas, UK; Kumar, A; Roy, A (Nepal Journal of Dermatology, Venereology & Leprology, 2013)
DOI: http://dx.doi.org/10.3126/njdvl.v11i1.7931 Nepal Journal of Dermatology, Venereology & Leprology Vol.11(1) 2013 pp.20-27